SDSS-V black hole mapper: the index diagram as a tool to disentangle the influence of the host galaxy in quasar spectra - Negrete, Castalia Alenka; Sandoval-Orozco, R; Ibarra-Medel, H; Tapia-Benavides, B I; Assef, R J; Dultzin, D; Lacerna, I; Morrison, S; Anderson, S F; Rodríguez Hidalgo, P; Aydar, C; Bauer, F E; et al. (Monthly notices of the Royal Astronomical Society, 2025)
We revisit the Quasar Main Sequence (QMS) by investigating the impact of the stellar component from the host galaxy (HG) on the emission line spectra of the active galactic nuclei (AGNs). We first detect spectra with broad emission lines using a line ratio method for a sample of $\simCastalia Negrete high SNR ($>$20) black hole mapper objects (part of the fifth phase of the Sloan Digital Sky Survey). We then built the Index diagram, a novel diagnostic tool using the z-corrected spectra, model-free, designed to easily identify spectra with significant stellar HG contributions and to classify the AGN spectra into three categories based on AGN-HG dominance: HG-dominated (HGD), Intermediate (INT), and AGN-dominated (AGND) sources. A colour-z diagram was used to refine the AGN-HG classification. We subtract the stellar contributions from the HGD and INT spectra before modelling the AGN spectrum to extract the QMS parameters. Our QMS reveals that HGD galaxies predominantly occupy the Population B region with no R$_{\rm {Fe\,{\small II}}}$, with outliers exhibiting R$_{\rm {Fe\,{\small II}}}$ $>$ 1, likely due to HG subtraction residuals and a faint contribution of h$β _{\rm BC}$. INT and AGND spectra show similar distributions in the Population A region, while in Population B, a tail of AGND sources becomes apparent. Cross-matching with radio, infrared, and X-ray catalogues, we find that the strongest radio emitters are associated with HGD and INT groups. Strong X-ray emitters are found in INT and AGND sources, also occupying the AGN region in the Wide-field Infrared Survey Explorer colour diagram.
Veröffentlicht: 08. Oktober 2025
Gesehen am 02.01.2026